HUBUNGAN PENGETAHUAN IBU TENTANG COVID-19 DENGAN KUNJUNGAN IMUNISASI PADA MASA PANDEMI - Tri Puspa Kusumaningsih (JURNAL MEDIKA USADA, 2022)
Background: The Covid-19 pandemic period is a worrying time, especially for mothers who have babies and toddlers. Meanwhile, immunization is very important for infants and toddlers to prevent various dangerous diseases. Based on a preliminary study conducted at the Kaligesing Health Center in Purworejo, immunization during the 2020 pandemic experienced a decrease in the achievement of the targeted number of targets, compared to the achievements and targets in 2019 before the pandemic. Objective: This study aims to determine the relationship between mother's knowledge about covid-19 and immunization visits during the pandemic in the Kaligesing Health Center area Methods: This type of research is correlative with a cross sectional approach. Population 341 respondents, sample 77 respondents. Purposive sampling technique. Test data analysis using Chi-square test with computerized SPSS Version 26.00 program. The research instrument used a questionnaire. Results: From the results of research and test data analysis obtained the value of Asymp.Sig. (2-sided) (0.002) < (0.05), meaning that there is a relationship between mother's knowledge about covid-19 and immunization visits during the pandemic Conclusion: There is a relationship between the mother's level of knowledge about covid-19 and immunization visits during the pandemic in the Kaligesing Health Center area.